Motivating adult learners: development and validation of the Self-Determined Motivations for Sexual Learning Scale (MSL) - Kim, Ju Ann (My University, 2025)
In the United States, the average age at which Americans receive formal sex education (i.e., sex-ed) is just 12 years old (SIECUS, 2024) with continuing education being informal or entirely non-existent. As sexuality is an ongoing process of development throughout the lifespan, engagement in adult sexual education is crucial yet often hindered by competing priorities, discomfort related to sexual topics, disinterest, or lack of accessibility. Compounding the problem, there is currently no empirically supported tool to measure motivation specifically for sexual learning. Guided by self-determination theory (SDT), the purpose of this study is to develop and validate the Self-Determined Motivations for Sexual Learning scale (MSL) designed to assess adults’ motivations for sexual learning. Exploratory and confirmatory analyses supported a four-factor model of motivation—autonomous, introjected, external, and amotivation—that theoretically aligned with SDT’s motivation continuum. Empirical testing found initial evidence for the reliability and validity of this measure within a diverse sample varying in age and ethnicity. Key findings include autonomous motivation being positively associated with self-determined motivations for sex, sexual satisfaction and assertiveness, and perceived importance of sex-ed. In contrast, introjected, external, and amotivated motivations for sexual learning were associated with greater sexual distress, embarrassment, and reduced sexual assertiveness. These findings support the psychometric soundness of the MSL scale and underscore the critical role of examining motivational quality in adult sexual learning. The MSL offers a practical tool for assessing motivational profiles, informing curriculum development, and evaluating program effectiveness. This study seeks to contribute to the emerging field of adult sexual education that is autonomy-supportive, personally meaningful, and culturally informed.
Keywords: Adult sex education; Scale development; Self-determination theory; Motivation; Measure; Sexual learning